Biologic therapies associated with development of palmoplantar pustulosis and palmoplantar pustular psoriasis: a systematic review. (6th February 2022) - Lu, Justin D.; Lytvyn, Yuliya; Mufti, Asfandyar; Zaaroura, Hiba; Sachdeva, Muskaan; Kwan, Sarah; Abduelmula, Abrahim; Kim, Patrick; Yeung, Jensen
Abstract: Background: Palmoplantar pustulosis (PPP) and palmoplantar pustular psoriasis (PPPP) are chronic inflammatory skin conditions characterized by eruptions of sterile pustules on the palms and/or soles. Biologic use has been associated with PPP and PPPP development in the literature. Objectives: To identify PPP and PPPP associated with biologics and summarize reported treatments and outcomes. Methods: We systematically searched in MEDLINE and Embase for articles that reported PPP or PPPP during biologic treatment. After a full‐text review, 53 studies were included for analysis. Results: We identified 155 patients with PPP/PPPP onset during biologic treatment, with a mean age of 44.1 years and a female preponderance (71.6%). The most frequently reported biologics were adalimumab (43.9%) and infliximab (33.3%). IL‐17 inhibitors, secukinumab (7.6%) and brodalumab (1.5%), were reported only in association with PPPP. Overall, 58.8% of patients had complete remission (CR) in 3.6 months and 23.5% had partial remission (PR) in 3.7 months. The most common treatments that led to CR were topical corticosteroids ( n = 16) and biologic switching ( n = 8). Conclusions: Clinicians should anticipate PPP or PPPP as potential drug reactions to biologics such as adalimumab and infliximab. Large‐scale studies are required to confirm our findings and further explore the pathogenesis for biologic‐associated PPP and PPPP.